The Physiology, Pathology, and Therapeutic Interventions for ROCK Isoforms in Diabetic Kidney Disease - Matoba, Keiichiro; Takeda, Yusuke; Nagai, Yosuke; Sekiguchi, Kensuke; Yokota, Tamotsu; Utsunomiya, Kazunori; Nishimura, Rimei (Frontiers in Pharmacology, 2020)
Rho-associated coiled-coil-containing protein kinase (ROCK) is a serine/threonine kinase that was originally identified as RhoA interacting protein. A diverse array of cellular functions, including migration, proliferation, and phenotypic modulation, are orchestrated by ROCK through a mechanism involving cytoskeletal rearrangement. Mammalian cells express two ROCK isoforms: ROCK1 (Rho-kinase β/ROKβ) and ROCK2 (Rho-kinase α/ROKα). While both isoforms have structural similarities and are widely expressed across multiple tissues, investigations in gene knockout animals and cell-based studies have revealed distinct functions of ROCK1 and ROCK2. With respect to the kidney, inhibiting ROCK activity has proven effective for the preventing diabetic kidney disease (DKD) in both type 1 and type 2 diabetic rodent models. However, despite significant progress in the understanding of the renal ROCK biology over the past decade, the pathogenic roles of the ROCK isoforms is only beginning to be elucidated. Recent studies have demonstrated the involvement of renal ROCK1 in mitochondrial dynamics and cellular transdifferentiation, whereas ROCK2 activation leads to inflammation, fibrosis, and cell death in the diabetic kidney. This review provides a conceptual framework for dissecting the molecular underpinnings of ROCK-driven renal injury, focusing on the differences between ROCK1 and ROCK2.